A simbologia da serpente no antigo oriente próximo, na Sagrada Escritura e na literatura extracanônica. - Pessoa, Cleandro de Oliveira (2020)
The present research, whose methodology consisted of bibliographical consultation, aims to expose the symbology of the snake used, initially, in the Ancient Near East, with emphasis on three ancient civilizations: Mesopotamia, Egypt and Canaan, examining their religions, divinities, rituals and mythologies, and the serpent as a symbol of creation, chaos, wisdom, power and healing. Then, we sought to understand the symbolism of the serpent in the context of the Old Testament, in the books of Genesis, Numbers, Job, Isaiah and in the Book of Wisdom; in extracanonical literature, in the Books of Enoch, Book of Jubilees, First and Second Book of Adam and Eve, Cave of Treasures and in the Apocalypse of Abraham. In the New Testament the study looked at the Gospels of Matthew, Mark, Luke and John, as well as at the Pauline writings and the Apocalypse, in which the serpent is seen as a dragon, a devil and as Satan. In this research, a better understanding is sought of those biblical texts that deal with this ambiguous yet intriguing figure that can embellish and attract; can represent both life and death; good as well as evil; temptation and salvation; a figure that is enigmatic and full of meanings.